Service quality model in determining the factors affecting user satisfaction towards GrabCar Service in Sungai Petani / Muhammad Faris Anuar Abdul Halim and Nurul Amirah Amalia Md Zulpakar - Abdul Halim, Muhammad Faris Anuar; Md Zulpakar, Nurul Amirah Amalia (2019)
This chapter focuses on the background of the study which is the factor affecting user satisfaction towards GrabCar service in Sungai Petani. This chapter has introduced the five dimensions on services quality that will influence the user satisfaction towards GrabCar service. Besides, it emphasized the problems that arise in the GrabCar service, research background, problem statement and the objectives for this study and define the term. In addition, the hypothesis of the study, the significance of the study, and the conclusion of the chapter.